Catheter salvage strategies in children with central venous catheter-related or -associated bloodstream infections: a systematic review and meta-analysis. (July 2022) - Buonsenso, D.; Salerno, G.; Sodero, G.; Mariani, F.; Pisapia, L.; Gelormini, C.; Di Nardo, M.; Valentini, P.; Scoppettuolo, G.; Biasucci, D.G.
Summary: Background: Optimal management of central venous catheter-related, or -associated, bloodstream infections (CRBSI or CLABSI) in children is not established. Aim: To evaluate success of catheter salvage strategies in paediatric patients. Methods: Studies were retrieved from medical databases and article reference lists. Data were collected relating to clinical outcomes of two treatments: systemic antibiotics alone or in association with antimicrobial lock therapy (ALT). Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated from a mixed logistic effects model. Heterogeneity was summarized using I 2 statistics. Publication bias was investigated by Egger's regression test and funnel plots. Findings: From 345 identified publications, 19 met inclusion criteria (total of 914 attempted salvage strategies). To achieve successful catheter salvage, in CRBSI the addition of ALT was superior to systemic antibiotics alone (OR: –0.40; 95% CI: –1.41, 0.62): 77% (95% CI: 69, 85; I 2 = 42.5%; P = 0.12) and 68% of success (95% CI: 59, 77; I 2 = 0; P < 0.05), respectively. CRBSI recurrence was less common in studies that used ALT compared with systemic antibiotics alone: 5% (95% CI: 0, 13; I 2 = 59.7%; P = 0.03) and 18% of recurrence (95% CI: 9, 28; I 2 = 0; P < 0.05), respectively. Recurrences were low with both antibiotic locks and ethanol lock. No clear benefits of ALT addition compared to systemic antibiotic only were found in CLABSI (OR: –0.81; 95% CI: –0.80, 2.43). Conclusion: The addition of an antimicrobial lock solution to systemic antibiotic may be beneficial for successful catheter salvage in paediatric patients with CRBSI, depending on aetiology, whereas no statistically significant difference between systemic antibiotic with or without addition of an antimicrobial lock solution was found regarding CLABSI.